Factibilidad para la creación de la unidad de archivo central del Gobierno Autónomo Descentralizado Municipal del cantón La Maná - Peñafiel Muñoz, Lilian Germania (2012)
This paper aims to determine the feasibility of the creation of the Central Archives Unit of the Gobierno Autonomo Descentralizado del Canton La Maná, with the aim of improving the administrative control of documents. For which the following objectives: to use the logical framework matrix, as an identification tool to the current situation on the administration of the files in each one of the departments and units, incorporating all the needs and views of stakeholders involved in this project, perform market research in order to establish the projected unmet demand for the creation of the Central Archives Unit, conduct a technical study for the creation of the Central Archives Unit and develop the economic study for the creation of Central File Unit. Among the methods applied were analytical and synthetic (deductive and inductive) for the problem. The universe is made up of citizens and public officials who work in the Gobierno Autonomo Descentralizado del Canton La Maná, in a number of 12,385 inhabitants and 34 staff, for which it was necessary to apply a formula of probability of 5%, which calculated the sample of 373 citizens, 15 Heads of Areas and 19 secretaries, to which it applied the surveys and observation. How was used as instruments for gathering the necessary information in the development of this research. For the implementation of this research, a nonparametric statistics yielded the same results, conclusions and recommendations. Where it was established that the majority population of users feel the service offered by the institution, it is slow and delayed, where a process can take several hours and days which it has caused dissatisfaction among citizens, problems caused by the disorder documentation, which undermines the efficiency of public processes, whose origin is the lack of a Central File Unit. The proposal includes the creation of the Central Archive Unit in Gobierno Autonomo Decentralizado del Canton La Maná, which is required for the design of the organizational structure of the proposed file unit, selecting the Institution staff to fill the Municipal charges required by the area in question, defining their duties and establishing policies and procedures to improve the performance of human talent, maximizing the efficiency of the processes of service offered to the public, for the benefit of the good life and the quality of the local population. To operate the unit in the Central Archive of the Gobierno Autonomo Descentralizado del canton La Maná, required material, financial, administrative and eminently human. being necessary investment in human. talent, so it raises the Induction and evaluation personnel. The proposal has economic feasibility because it has a rate of 41.31% IRR and NPV equals $ 45,360.75 that exceeds the initial investment of $ 22,181.25, with a recovery time of investment equal to three years, demonstrating the feasibility implementing economic File Unit in The Gobierno Autonomo Descentralizado Municipal de La Maná. The total fixed investment to implement the creation of the file unit is $ 22,181.25, a net present value (NPV) of $ 45,360.75 which exceeds the initial investment and a recovery time of investment equal to 3 years, demonstrating the economic feasibility of the proposal, which after approval by the authorities of the Gobierno Autonomo Descentralizado Municipal del canton La Maná, will account for its execution.